2021
DOI: 10.3389/fonc.2021.730093
|View full text |Cite
|
Sign up to set email alerts
|

Exosome Released FZD10 Increases Ki-67 Expression via Phospho-ERK1/2 in Colorectal and Gastric Cancer

Abstract: Frizzled (FZD) proteins are primary receptors for Wnt signaling that activates the mitogen-activated protein kinase (MAPK) pathways. Dysfunction of Wnt signals with consequently abnormal activation of MAPK3 pathways was found in colorectal cancer (CRC) and gastric cancer (GC). Upregulation of FZD10 protein, localized in the exosomes isolated from plasma of CRC and GC patients, was associated with a poor prognosis. Herein, the expression levels of circulating FZD10 were found to be strongly correlated to their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Ki-67 nucleoprotein is an indicator of cell growth fraction and a marker-related to cell proliferation activity [ 22 ]. Previous studies have demonstrated that Ki-67 expression was related with proliferation and metastasis of CRC [ 23 , 24 ]. In our study, FGF12 knockdown decreased the expression of Ki-67 in vivo and in vitro experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Ki-67 nucleoprotein is an indicator of cell growth fraction and a marker-related to cell proliferation activity [ 22 ]. Previous studies have demonstrated that Ki-67 expression was related with proliferation and metastasis of CRC [ 23 , 24 ]. In our study, FGF12 knockdown decreased the expression of Ki-67 in vivo and in vitro experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Ki-67 is closely related to cell proliferation and ribosome transcription and is often used to assess the level of tumor proliferation. If the gastric mucosa expresses Ki-67, it indicates the occurrence of Dys[ 22 ]. XJZ improved the general condition of GPL rats, reduced the degree of gastric mucosal injury and pathology, inhibited CDX-2 and Ki-67 expressions in gastric mucosa, adjusted serum MDA and SOD levels associated with oxidative stress injury, and protected the gastric mucosal barrier.…”
Section: Discussionmentioning
confidence: 99%
“…FZD10 is among the genes that are aberrantly expressed in the Wnt signaling pathway. Previous studies have shown that FZD10 is involved in the progression of several types of cancer, including colorectal cancer, gastric cancer, and synovial sarcomas ( 39 – 41 ). Additionally, a therapeutic targeting FZD10 (OTSA101) is currently in clinical trials ( 42 ).…”
Section: Discussionmentioning
confidence: 99%